Processos identitários e a recriação de desigualdades sociais no entorno de uma unidade de conservação : um estudo sobre os oleiros dos povoados Rio das Pedras - Schettino, Gregorio Cerqueira (2014)
As part of the work of the research Group Identity Processes and Power (GEPPIP / UFS) that has been studying the changes introduced with the creation of the Serra de Itabaiana National Park (PARNASI) in the life of communities from their surroundings, in this research set out what has changed in relation to values and representations about the work in brick factory, which contributes to the process of potters´s identification from the village Rio das Pedras, that is located in the vicinity of the Conservation Unit has been cited before. For it, it were used the concepts of identity from authors such as Stuart Hall, Castells and Claude Dubar besides Canclini´s hybridisation and intercultural. To achieve these goals, the data collection has conducted through semi-structured interviews. The search had pointed that the process of identification of potters left of the exclusion vision about their work. The image that the closest interlocutors as residents, potters and public agency have about the work in the brick factory is subsistence, an informal activity that generates income to a needy population and without training. The situation of inequality, disconnection and exclusion is the factor that doesn´t allow regularizing in front of tax, labor and environmental laws. So that the creation of the PARNASI can´t be seen in isolation as a factor that puts the potters as irregular, because they come from a marginalized situation from a different way of the logic modernity production.